1981
DOI: 10.3354/meps004069
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Composition of Some Typical North Sea Copepods

Abstract: Copepods of the southern North Sea and Wadden Sea were investigated with special respect to the main lipid groups as well as to their fatty-acid pattern. The seasonal variation of lipids of the small copepods Temora longicornjs, Acartia clausi and Centropages hamatus was determined; in addition some zooplankters, which could only b e sampled sporadically, were analysed. The seasonal values for total lipids from the small copepods varied between 0,3 and 1 pg ind.-', with maximal concentrations during spring and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…The rather limited ingestion of diatoms seems to be characteristic for temperate regions, as all studies show similarly low marker amounts (Kattner et al 1981;Kattner and Krause 1989;Fraser et al 1989;Cotonnec et al 2001). Still, the levels of 16:1(n¡7) found in our study belong to the lowest ever measured for Pseudocalanus spp., indicating a more intense use of other food sources.…”
Section: Trophodynamicssupporting
confidence: 45%
See 1 more Smart Citation
“…The rather limited ingestion of diatoms seems to be characteristic for temperate regions, as all studies show similarly low marker amounts (Kattner et al 1981;Kattner and Krause 1989;Fraser et al 1989;Cotonnec et al 2001). Still, the levels of 16:1(n¡7) found in our study belong to the lowest ever measured for Pseudocalanus spp., indicating a more intense use of other food sources.…”
Section: Trophodynamicssupporting
confidence: 45%
“…(e.g. Kattner et al 1981;Kattner and Krause 1989;Fraser et al 1989;Norrbin et al 1990;Cotonnec et al 2001), we found 18:1(n¡9) to be one of the most abundant fatty acids throughout the year. Apparently, this does not inevitably indicate similar feeding habits in diVerent habitats, but rather a species-speciWc attribute, probably aVected by metabolic processes.…”
Section: Trophodynamicsmentioning
confidence: 60%
“…1; The differences between the mesozooplankton samSerrazanetti e t al. 1994a, b), the Baltic Sea (Finnish ples from Stn SJ107 and from the other 3 compared coastal waters; Kaitaranta et al 1986), and the southregions were not statistically significant for most of the ern North Sea and Wadden Sea (Kattner et al 1981).…”
Section: Comparisons Between Marine Regionsmentioning
confidence: 97%
“…Fatty acid composition of the mesozooplankton natural community depends on sea depth and temperature, geographical location, and season, particularly in relation to food availability, and can vary greatly during zooplankton starvation (Lee et al 1971, Morris 1971, Lee 1974, Kattner et al 1981, Kattner 1989, Serrazanetti et al 1994b, Ederington et al 1995. Zooplankton starvation can occur during unusual events in the marine environment, like the massive appearance of mucilaginous aggregates in the northern Adriatic (Malej 1995).…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that MUFA (18:1 n-9 and 16:1 n-7) reached high proportions but PUFA is the dominant fatty acid in Rhincalanus gigas. Kattner et al (1981) measured the fatty acid content of Pseudocalanus elongatus and Calanus finmarchicus. They found that in P. elongates SFA was 54.1±6.4%, MUFA was 31.0±7.4% and PUFA 14.8±4.9%, and in C. finmarchicus SFA was 52.2±7.6%, MUFA 19.1±2.5% and PUFA 28.7±10.1%.…”
Section: Fatty Acid Profilementioning
confidence: 99%